Media Online Store Dengan Penerapan E-CRM Di Susi Bucket And Decoration - Dian Kartini; Fauriatun Helmiah; Wan Mariatul Kifti (Jurnal Algoritma, 2026)
The development of digitalization encourages MSMEs to optimize their sales and customer relationship management systems in an integrated manner. Susi Bucket and Decoration still faces obstacles in order management, customer data recording, and market reach limitations due to manual processes. This study aims to design and implement an Electronic Customer Relationship Management (E-CRM)-based Online Store system to improve operational efficiency and customer service quality. The methods used are a descriptive qualitative approach with a Waterfall system development model and testing using the black box method. The results show that the system is capable of centrally integrating transaction and customer data, accelerating the order recording process by an average of ±3 minutes compared to the manual method, and improving customer response effectiveness through chat and structured review features. Additionally, period-based sales reports help business owners systematically evaluate sales trends. The scientific contribution of this research lies in the development of an integrated E-CRM implementation model for creative SMEs that combines digital transactions, customer satisfaction monitoring, and sales analytics in a single integrated platform.